PENDEKATAN ESTETIKA PADA DESAIN PESAN MULTIMEDIA PEMBELAJARAN - Moeljadi Pranata (Fakultas Sastra Universitas Negeri Malang, 2013)
The development of multimedia design is influenced by various theories such as visual aesthetic principles. Aesthetic principles are used to guide the design process as well as play a role to increase the attractiveness of the message. However, along with the progress in computer graphics, graphic design aesthetic applications in multimedia learning has led to the concept of multimedia performances entertaining, aesthetic oriented. Additionally, this technology, along with multimedia technology, has expanded the field of professional designing multimedia learning beyond learning profession such as graphic designer profession.